Efficient market hypothesis in European stock markets - Borges, Maria Rosa (2010)
This paper reports the results of tests on the weak-form market efficiency applied to stock market indexes of France, Germany, UK, Greece, Portugal and Spain, from January 1993 to December 2007. We use a serial correlation test, a runs test, an augmented Dickey-Fuller test and the multiple variance ratio test proposed by Lo and MacKinlay (1988) for the hypothesis that the stock market index follows a random walk. The tests are performed using daily and monthly data for the whole period and for the period of the last five years, i.e., 2003 to 2007. Overall, we find convincing evidence that monthly prices and returns follow random walks in all six countries. Daily returns are not normally distributed, because they are negatively skewed and leptokurtic. France, Germany, UK and Spain meet most of the criteria for a random walk behavior with daily data, but that hypothesis is rejected for Greece and Portugal, due to serial positive correlation. However, the empirical tests show that these two countries have also been approaching a random walk behavior after 2003.